PEMBUATAN E-KATALOG SEBAGAI MEDIA PROMOSI DIGITAL UMKM WARGA RW 03 KELURAHAN MANYAR SABRANGAN - Az Zahra, Sabrina Aulia; Remalya, Asiel Bernike; Rahmatin, Leily Suci (LPPM Universitas Nusa Mandiri, 2025)
Indonesia, with a population of around 270 million, has great potential to develop its economy through the utilization of existing resources. However, the challenges in strengthening the economy are still great, especially with the rapid development of technology 4.0 which affects the dissemination of information. Digital marketing strategies are key to driving economic growth, especially for MSMEs that often still use conventional marketing methods. Observation results show that many MSMEs face difficulties in implementing digital marketing due to lack of knowledge and skills. This community service activity was carried out in RW 03, Manyar Sabrangan Village, Surabaya, to help MSMEs switch to digital marketing by creating an e-catalog that can be accessed via QR code. The method used is a participatory method with a community approach. Community service activities involve collecting product data, creating designs using digital devices, and handing over and assisting in the use of e-catalogs to MSMEs. Evaluation was carried out to assess the effectiveness of the use of e-catalogs by MSMEs. The implementation of e-catalogs showed an increase in operational efficiency and market reach for MSMEs. This program is expected to provide a significant positive impact, strengthen the position of MSMEs through effective promotional strategies, and increase the capacity of human resources in business management and digital marketing.